KECENDERUNGAN PEMANFAATAN MEDIA SOSIAL SEBAGAI SUMBER INFORMASI KESEHATAN OLEH PETANI DI DESA DAWUHAN LOR: THE TREND OF USING SOCIAL MEDIA AS A SOURCE OF HEALTH INFORMATION BY FARMERS IN DAWUHAN LOR VILLAGE - Ningrum, Teysya Dwi; Purwandari, Retno; Tri Afandi, Alfid; Wijaya, Dodi; Muhammad Nur, Kholid Rosyidi (BIMIKI (Berkala Ilmiah Mahasiswa Ilmu Keperawatan Indonesia), 2024)
Introduction: Social Media has become an important tool in spreading health information, providing benefits for public health including for an easily accessible source of information for all. Farmers are a vulnerable group but they often ignore health problems and prefer self-diagnosis through electronic media or leave it alone. Methods: The purpose of this study was to find an overview of the trend of social media use as a source of health information by farmers in Dawuhan Lor Village. This study used quantitative descriptive method. Sampling technique used is purposive sampling with the number of respondents as many as 91 people. Data collection was carried out using personal instruments that have been adapted from Social Media Use and Computer Survey. Result: The results showed that the tendency of the use of social media as a source of information by farmers is in the medium category. This includes three indicators of the source of information sought such as treatment search, disease, and access to health services which are also in the medium category. Conclusion: Farmers use social media to search for information, interact with others, and utilize certain features, but they are not entirely dependent on social media as a source of information. Social media plays an important role as a component in "Cues to Action," influencing health decision-making processes at both individual and community levels. Information obtained through these digital platforms can significantly influence individual behavior in their efforts to promote and manage their health.